Peningkatan Hasil Belajar Materi Tajwid melalui Metode BBM - Tutik Haryanti (MGMP PAI SMP BINTAN, 2023)
This article is focused on improving student learning outcomes on the law of reading qalqalah and ra with the methods of playing, discussing and reciting. This study aims to determine the extent to which the effectiveness of the BBM method can improve student learning outcomes in the material for reading qalqalah and ra. To answer this question, this study uses action research. The research participants were students of class VII in junior high school. The ability to read the Qur'an should be possessed by every student. Students must have the ability to recite the words of Allah SWT. In reading the Qur'an, it must be in accordance with its makhraj. Therefore an understanding of the science of recitation must be mastered by every student so that in reading the Qur'an one can avoid mispronunciation. The data analysis shows that students have low learning outcomes before the action is taken but shows a significant increase in learning outcomes after experiencing the action. This study can make a positive contribution to PAI teachers in the future.